Electrochemical Performance of Hybrid Cationic Aqueous-Based Rechargeable Battery with Different Current Collectors and Electrolytes. (23rd December 2019) - Chen, Shang; Tang, Fang; He, Ting; Zhang, Huanhuan; Deng, Shanshan; Li, Yukang; Wu, Xianwen; Zhang, Qiaobao; Xiang, Yanhong; Yan, Wenbin
Abstract : Different zinc foils as anode current collectors by electrowinning in various electrolytes with additives were prepared, which were evaluated through X-ray diffraction (XRD), scanning electron microscopy (SEM), float charge, and Tafel curve tests. The effect of different cathode current collectors, electrolytes, and the as-prepared zinc foils as the anode on the coulombic efficiency and the cycling performance of aqueous batteries were investigated. The results indicate that the initial coulombic efficiency and discharge capacity of the battery with 1 mol/L ZnSO4 and 2 mol/L Li2 SO4 are 94.31% and 105.7 mAh/g using graphite as the current collector, which are much higher than 68.20% and 71.0 mAh/g using conductive polyethylene, respectively, attributed to the smaller polarization and electrochemical transfer impedance ( R ct ) of the former. However, the capacity retention of the latter is much higher than that of the former, especially using the high-concentration-lithium-based hybrid electrolyte, of which it is up to 74.63% even after 500 cycles. Moreover, the cycling performance of a battery with as-prepared zinc foil adding thiourea and gelatin into electrolyte during electrowinning is much better than that without additives, which is due to the smaller corrosion rate and side reaction.